2019
DOI: 10.3390/antiox8100486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Storage Time and Temperature on Lipid Oxidation and Protein Co-Oxidation of Low-Moisture Shredded Meat Products

Abstract: Studies on the oxidative changes in meat-based, low-moisture, ready to eat foods are complicated due to complex food system and slow lipid-protein oxidative deterioration. The current study evaluates the oxidative changes over six months of storage on shredded beef and chicken products (locally known as serunding) for physicochemical analysis, lipid oxidation (conjugated dienes and malondialdehydes) and protein co-oxidation (soluble protein content, amino acid composition, protein carbonyl, tryptophan loss and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…The highest amount of MDA and the slope of changes were related to vegetable oils with polyunsaturated chains such as canola and sun ower for cooking. The higher the ratio of PUFA and MUFA fatty acids in oils, the higher the MDA production [34]. It was also found that the lowest amount of MDA before cooking and the slope of changes over a period of time are related to Kermanshahi oil and the combination of Kermanshahi oil with frying oil, which indicates that the higher the SFA in oils, the lower the amount of MDA [35].…”
Section: Discussionmentioning
confidence: 87%
“…The highest amount of MDA and the slope of changes were related to vegetable oils with polyunsaturated chains such as canola and sun ower for cooking. The higher the ratio of PUFA and MUFA fatty acids in oils, the higher the MDA production [34]. It was also found that the lowest amount of MDA before cooking and the slope of changes over a period of time are related to Kermanshahi oil and the combination of Kermanshahi oil with frying oil, which indicates that the higher the SFA in oils, the lower the amount of MDA [35].…”
Section: Discussionmentioning
confidence: 87%
“…Higher ROS levels lead to significant mitochondrial dysfunctions and oxidative stress [ 4 , 38 , 57 ]. Studies in chickens have also shown that high temperatures induce both oxidation of lipids and proteins [ 58 , 59 ]. However, in another study assessing the effect of acute and chronic HS on chickens, no changes in both lipid and protein oxidation were observed [ 60 ].…”
Section: Heat Stress and Oxidative Stress In Broiler Chickensmentioning
confidence: 99%
“…The terminated free radicals were conjugated (i.e., radical-radical interaction). Moreover, lipid radicals (lipid oxidation) can also abstract hydrogen from protein functional groups, which can result in lipid protein cross-linking [36], suggesting a possible reduced capacity for protein and lipid oxidation via the indirect effect of radicals from the heating method.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%